The elusive pervasiveness of english in higher education : the case of Colombia (2020)
ABSTRACT: This article aims at describing how the educational actors of a private university make sense of language policies.The research was guided under a qualitative approach taking the historic-hermeneutic perspective as a paradigm. The data collected consists of news and information about the National Foreign Language Policy, the text corpus supporting the institutional policy, and semi-structured interviews. The results show how participants, albeit the pervasiveness of language policies in all the national educational system, conceive English far off from being necessary for professional life as the government intends. The study concluded that is imperative to take stances in the analysis and the enactment of language policies in order to obtain better results.